“ANAK HEBAT, AYO CEK MATA”: A PROGRAM OF VISUAL ACUITY SCREENING IN CHILDREN OF SIDOREJO VILLAGE - Anthony Camilo Lim; Ahmad Adani Thirafi Yusuf; Nafla Rafida Syifa; Firnida Hanan Nurkhalisha; Enrico Rabbani Putra; Almira Felicia Wijayakusuma; Aina Cahyaning Santoso; Salsabila Shafa Qonita; Nabila Putri Naila; Inna Kuswandari (Universitas Airlangga, 2025)
Visual impairment in children is a health issue that affects cognitive, social, and educational development, yet early detection at the preschool level is still rarely implemented. The community service program “Anak Hebat: Ayo Cek Mata!” was conducted to address this need in Sidorejo Village, Gresik Regency, where no previous screening of visual acuity had been carried out among children in Playgroup (KB) and Kindergarten (TK) or equivalent levels. The aim of this activity was to detect visual acuity problems early in preschool children so that timely referral and management could be provided. The implementation method consisted of four stages: needs identification through interviews with village officials and schools, activity planning through coordination with stakeholders, visual screening using the Peek Acuity application with standardized measurement procedures, and evaluation of activity. Data were analyzed descriptively and inferentially, including Fisher’s exact test. A total of 56 children participated, but only 39 children (69.6%) were successfully assessed for visual acuity. There was a significant association between age and measurement success (p<0.001). Among children with successfully measured visual acuity, 37 (94.8%) had no visual impairment, 1 child (2.6%) had mild impairment, and 1 child (2.6%) had moderate impairment. No association was found between either age or sex and visual acuity classification (p=0.858 and p=0.231). The limitations of the activity included low cooperativeness among children aged 3–4 years and the absence of alternative methods for children who did not yet understand instructions. Nevertheless, this program provides long-term benefits for the community, including serving as a basis for school vision health policies, supporting village-level health program evaluation, and encouraging the establishment of routine screening initiatives. Early detection at the preschool age is expected to prevent worsening visual impairment and improve children’s quality of life in the future.